AC voltage regulation of a bidirectional high-frequency link converter using a deadbeat controller - Toh, L. S.; Ramli, M. Z.; Salam, Zainal; Elbuluk, M. E. (IEEE, 2006)

(untitled)
This paper presents a digital controller for AC voltage regulation of a bidirectional high-frequency link (BHFL) inverter using Deadbeat control. The proposed controller consists of inner current loop, outer voltage loop and a feed-forward controller, which imposes a gain scheduling effect according to the reference signal to compensate the steady-state error of the system. The main property of the proposed controller is that the current- and the voltage-loop controllers have the same structure, and use the same sampling period. This simplifies the design and implementation processes. To improve the overall performance of the system, additional disturbance decoupling networks are employed. This takes into account the model discretization effect. Therefore, accurate disturbance decoupling can be achieved, and the system robustness towards load variations is increased. To avoid transformer saturation due to low frequency voltage envelopes, an equalized pulse width modulation (PWM) technique has been introduced. The proposed controller has been realized using the DS1104 digital signal processor (DSP) from dSPACE. Its performances have been tested on a one kVA prototype inverter. Experimental results showed that the proposed controller has very fast dynamic and good steady-state responses even under highly nonlinear loads.